Relação professor/livro didático: impactos na abordagem do movimento retilíneo uniforme - (:unkn) unknown (Universidade Federal do Pampa, 2017)
Science Nature education is characterized by the integration of three areas of knowledge: Physics, Chemistry and Biology. Specifically the last year of elementary school presents in your curriculum contents of theses three areas, which will serve as basis for these same curricular components taught in later years in high school. In particular, the teaching of Physics in contemporary basic education is still outdated in terms of content and technologies, based, in large part, only in a textbook or booklet. For the reason that the textbook (LD) remains significantly supporting the teaching practice, this research directs to the the content of Rectilinear Uniform Motion (MRU), generally extracted by teachers from the LDs in last year of elementary school. In an attempt to reflect on the conceptions attributed by teachers to the LD of Sciences, we opted to analyze their discourses, aiming to understand the relationship between their methodological approaches and LD contributions concerning the content of MRU which is provided in the curriculum of Municipal and State schools. In order to obtain greater clarity on the subject of study, we decided to develop a research with qualitative approach, a case study, through the application of questionnaires to science teachers of the last year of elementary school, acting in public Municipal and State schools in the municipality of Dom Pedrito/RS. The questionnaire the characterization of the subject of the research considering aspects of academic training of participants and with regard to the working time as a teacher at the school. The data collection instrument also investigated how LD guides the planning of the science teacher by looking at how seven practitioners use this resource in their classes. Thus, with a questionnaire, it was possible to describe the narratives of the subjects involved in the research. Based on the the answers an interpretation was made followed by a qualitative analysis and of the obtaned data, providing a close interaction with the conception of the investigated subjected, generating knowledge for practical application directed to the solution of specific problems. By means the theory of content analysis (BARDIN, 2015), it was noticed that the teachers of Sciences makes the MRU content approach based on the LD, however, the tools of Information and Communication technologies are gradually entering in the planning of teachers and in the work of room of class. With these results one can understand how the teacher / textbook relationship occurs and (analyze) to verify how this resource contributes to Science Teaching, and which the significant contribution in the learning and teaching process.
Keywords: Ciências; Física; Livro didático; Professor; Science; Physics; Textbook; Teacher; Ciências da natureza; Natural science; Educação; Education; CNPQ::CIENCIAS EXATAS E DA TERRA